The Columbia anthology of modern Japanese drama - Rimer, J. Thomas; Mori, Mitsuya; Poulton, M. Cody; Rimer, J. Thomas; Mōri, Mitsuya, 1937-; Poulton, M. Cody, 1955- (New York : Columbia University Press, 2014)
"An anthology of modern Japanese drama from the mid-nineteenth century to the early twenty-first century"-- (Provided by publisher.)
Also includes historical, critical commentaries.
boek
Keywords: Japanese drama -- 19th century -- Translations into English; Japanese drama -- 20th century -- Translations into English; Japanese drama -- 21st century -- Translations into English; Japanese drama -- 19th century -- History and criticism; Japanese drama -- 20th century -- History and criticism; Japanese drama -- 21st century -- History and criticism; Theater -- Japan -- History -- 19th century; Theater -- Japan -- History -- 20th century; Theater -- Japan -- History -- 21st century; Japan